The diagnosis of progressive supranuclear palsy: current opinions and challenges. (3rd July 2018) - Ali, Farwa; Josephs, Keith
ABSTRACT: Introduction : Progressive supranuclear palsy (PSP) is associated with microtubule-associated protein tau dysfunction. Originally thought to result in a syndrome of atypical Parkinsonism, vertical supranuclear gaze palsy, and cognitive impairment, several additional phenotypic manifestations of PSP pathology have been described over the last 20 years. Furthermore, prototypical PSP features may develop late, making early diagnosis challenging. Areas covered : An in-depth view of emerging knowledge in the field of PSP. Advances in clinicopathologic correlation, blood, cerebrospinal, and more importantly neuroimaging biomarkers are discussed in light of the 2017 PSP diagnostic criteria by the Movement Disorders Society Study Group. Discoveries related to molecular pathogenesis have enabled development of disease-modifying therapies for PSP, many of which are currently under investigation. Expert commentary : Despite remarkable growth in our knowledge of tauopathies like PSP, early and accurate clinical prediction of PSP neuropathology remains challenging. Clinical phenotypes overlap, and biomarkers are nonspecific. There is a pressing need for disease-specific biomarkers that enable timely identification of patients and biomarker-driven investigation of disease-modifying therapies.